2019
DOI: 10.1111/jce.13813
|View full text |Cite
|
Sign up to set email alerts
|

A multicentered evaluation of ablation at higher power guided by ablation index: Establishing ablation targets for pulmonary vein isolation

Abstract: Background Pulmonary vein isolation (PVI) using high power delivered by SmartTouch Surround Flow (STSF) catheters guided by ablation index (AI) was evaluated in a multicenter registry. Methods Patients with paroxysmal AF underwent PVI with STSF catheters using 30 W on the posterior wall and 40 W elsewhere. AI targets were 350 posterior walls and 450 elsewhere. Procedures were compared with controls using conventionally irrigated contact force‐sensing catheters using conventional powers (25 W posterior wall and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
130
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(144 citation statements)
references
References 31 publications
14
130
0
Order By: Relevance
“…Few data were reported on the clinical outcome of AI‐guided HP RF application in AF ablation. Recently, the proportion of patients free from atrial tachyarrhythmia recurrence after AF ablation with AI‐guided HP RF application (30 W on posterior walls and 40 W elsewhere) was reported to be higher compared with the FTI‐guided conventional setting (25 W posterior wall and 30 W elsewhere) . But no data on the clinical impact of HP and short‐duration RF application compared with LP and long‐duration RF application with same target AI has been shown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Few data were reported on the clinical outcome of AI‐guided HP RF application in AF ablation. Recently, the proportion of patients free from atrial tachyarrhythmia recurrence after AF ablation with AI‐guided HP RF application (30 W on posterior walls and 40 W elsewhere) was reported to be higher compared with the FTI‐guided conventional setting (25 W posterior wall and 30 W elsewhere) . But no data on the clinical impact of HP and short‐duration RF application compared with LP and long‐duration RF application with same target AI has been shown.…”
Section: Discussionmentioning
confidence: 99%
“…14 from atrial tachyarrhythmia recurrence after AF ablation with AIguided HP RF application (30 W on posterior walls and 40 W elsewhere) was reported to be higher compared with the FTI-guided conventional setting (25 W posterior wall and 30 W elsewhere). 13 But no data on the clinical impact of HP and short-duration RF application compared with LP and long-duration RF application with same target AI has been shown. Although a follow-up period was relatively short in this study (median 10.1 months in LP and MP and 6.5 in HP groups), we found no significant difference in AF-free survival rates among the three groups.…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that HPSD using STSFc is safe and led to shorter procedure times with a reduced acute PV reconnection as compared to conventional ablation. 35 Thus, the safe and efficacious application of HPSD using STSFc as identified by more clinical trials, informs us that STSFc might be widely applied in the future for AF ablation.…”
Section: Discussionmentioning
confidence: 99%
“…4 Increased power theoretically results in reduced RF application duration when there is a similar CF. [5][6][7][8][9] However, the use of higher power could also potentially increase the complication rate, the risk of steam pop or esophageal injury. 10 While historically the power was set below 35 W (mostly ≤ 25 W at the posterior wall), 1,11,12 recent studies using AI as targeted endpoint have shown promising results with a power ≥35 W. 9,13,14 In all three of these studies, STSF catheters were used (SmartTouch Surround Flow;…”
Section: Introductionmentioning
confidence: 99%